2018
DOI: 10.1186/s13104-018-3186-z
|View full text |Cite
|
Sign up to set email alerts
|

Medical student attitudes towards older people: a critical review of quantitative measures

Abstract: ObjectivesFurther research into medical student attitudes towards older people is important, and requires accurate and detailed evaluative methodology. The two objectives for this paper are: (1) From the literature, to critically review instruments of measure for medical student attitudes towards older people, and (2) To recommend the most appropriate quantitative instrument for future research into medical student attitudes towards older people.ResultsA SCOPUS and Ovid cross search was performed using the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…Despite being a potential weakness for validation of a new quantitative instrument, we did not believe demonstrating correlation with another scale would be constructive. Acknowledging some correlation between commonly used attitudes scales in a recent Brazilian study, our critical review of the international literature concluded there was insufficient evidence for validity of any of these scales in the Australian context …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Despite being a potential weakness for validation of a new quantitative instrument, we did not believe demonstrating correlation with another scale would be constructive. Acknowledging some correlation between commonly used attitudes scales in a recent Brazilian study, our critical review of the international literature concluded there was insufficient evidence for validity of any of these scales in the Australian context …”
Section: Discussionmentioning
confidence: 89%
“…A critical review of international literature regarding medical student attitudes towards older people led to selection of a semantic differential as the optimal quantitative instrument type to develop for Australian use . Widely employed internationally, the US‐developed instrument with this construct, the Ageing Semantic Differential (ASD), has been in use since 1969 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alquwez et al (11) cited that the nursing students that have a near contact to the grandparents, have also positive attitudes toward older peoples. Wilson et al (18) wrote that the medical studens had moderately positive attitudes towards older people. Cheong et al (19) demonstrated that the medical students in Singapore have a positive attitude towards the older people.…”
Section: Discussionmentioning
confidence: 99%
“…Working with older patients has often been described as a burden and as less satisfying than working with younger patients. Negative attitudes towards the elderly have been shown to be important predictors for the quality of care and treatment [13] and are one main reason why young medical professionals tend to avoid the field of geriatrics [14]. Recent studies suggest that medical students are not aware of who their future patients will be [11].…”
Section: Introductionmentioning
confidence: 99%